Soil in Prekmurje in the light of climate change - Ana Vovk Korže (Journal for Geography, 2020)
Given the importance of self-sufficiency on the one hand, and caring for natural resources such as soil and water on the other, it is increasingly important to know how soils are adapted to climate change from an ecosystem perspective. This means according to their properties, which significantly affect the ability to retain water, the presence of organic matter, denudation and erosion, and the ability to self-regenerate. Such properties are thickness, texture, organic matter, consistency and skeleton. As there are no quantitative data for all soils, we prepared an evaluation method based on their theoretical descriptions (from previous research) and classified them into unadapted, partially adapted and well adapted to climate change. In Prekmurje,unadapted and partially adapted soils to climate change predominate, which is a warning for land use planning in the future.